Discovering Westcave : The Natural and Human History of a Hill Country Nature Preserve - Caran, S. Christopher; Davenport, Elaine, 1946- (Book collections on Project MUSE., 2016)
In the heart of the Texas Hill Country lies an astonishing place called Westcave Preserve, a 76-acre nature preserve and environmental education facility in western Travis County, near Austin, that provides a sanctuary for the flora and fauna of surprisingly diverse ecosystems. Westcave has been connecting children and families to nature since 1976, when the nonprofit Westcave Preserve Corporation was established to restore and protect a popular but rapidly deteriorating picnic spot that encompassed a fern-covered grotto, an ancient rock shelter, and a spectacular forty-foot waterfall. In Disc.